Vývoj elektrochemického glutamátového biosenzoru - Doležalová, Julie (Univerzita Karlova, Ovocný trh 5, 116 36 Praha 1, http://cuni.cz/, 2007)
DEVELOPMENT OF A GLUTAMATE ELECTROCHEMICAL BIOSENSOR Julie Doležalová (Department of Analytical Chemistry, Faculty of Pharmacy, Charles University in Prague) In cooperation with: Sofia A.L.P. Gomes, Alberto N. Araújo (Department of Physical Chemistry, Faculty of Pharmacy, University of Porto) L-Glutamic acid and monosodium glutamate are used to enhance flavour in food prepared at home, restaurants, and by the food processing industry [1]. Glutamate also plays an important role in many metabolic processes. Nevertheless its use is being kept under certain limits as some people have experienced adverse effects, such as stiffness and tension, after its ingestion. Moreover, some studies demonstrate its connection with the appearance of neurological manifestations, such as Parkinson's and Alzheimer's disease. The determination of L-glutamic acid is therefore of major importance. In this work a novel L-glutamate biosensor was developed using a dehydrogenase enzyme (L-glutamate dehydrogenase). These redox enzyme requires for its activity nicotinamide (NAD(P)+ /NAD(P)H) coenzyme, which reduced form was electrochemically regenerated by the water-soluble dye, methylene green. Graphite electrodes were modified with a poly(methylene green) thin film by means of methylene green electrochemical polymerization...